Role of Active Efflux Proteins in the Defence of the Gastrointestinal Tract from Excessive Colonisation of Pathogenic Microflora - Warrier, Aparna (Curtin University, 2017)
The study examined the presence of antimicrobial peptides in human gastrointestinal cells linked to P-gp expression, based on earlier studies from this lab suggesting P-gp induction increased antimicrobial resistance in-vitro. This study established that effects were bacteriostatic not bacteriocidal, implying delayed attachment but influences of P-gp on expression of specific endogenous peptides was not clear. Amyloid beta-42 was not a substrate. Proteomic analysis of excreted proteins suggested histones may play a role in innate immunity.